The effect of silver nanoparticles (AgNPs) on proliferation and apoptosis of in ovo cultured glioblastoma multiforme (GBM) cells - Urbańska, Kaja (Nanoscale Res Lett, 2015)
Recently, it has been shown that silver nanoparticles (AgNPs) provide a unique approach to the treatment of tumors, especially those of neuroepithelial origin. Thus, the aim of this study was to evaluate the impact of AgNPs on proliferation and activation of the intrinsic apoptotic pathway of glioblastoma multiforme (GBM) cells cultured in an in ovo model. Human GBM cells, line U-87, were placed on chicken embryo chorioallantoic membrane. After 8 days, the tumors were divided into three groups: control (non-treated), treated with colloidal AgNPs (40 μg/ml), and placebo (tumors supplemented with vehicle only). At the end of the experiment, all tumors were isolated. Assessment of cell proliferation and cell apoptosis was estimated by histological, immunohistochemical, and Western blot analyses. The results show that AgNPs can influence GBM growth. AgNPs inhibit proliferation of GBM cells and seem to have proapoptotic properties. Although there were statistically significant differences between control and AgNP groups in the AI and the levels of active caspase 9 and active caspase 3, the level of these proteins in GBM cells treated with AgNPs seems to be on the border between the spontaneous apoptosis and the induced. Our results indicate that the antiproliferative properties of silver nanoparticles overwhelm proapoptotic ones. Further research focused on the cytotoxic effect of AgNPs on tumor and normal cells should be conducted. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s11671-015-0823-5) contains supplementary material, which is available to authorized users.